Pricing and calibration of Libor Market Model - Pozsonyiová, Daniela (2018)
This thesis focuses on models of interest rate, especially LIBOR market model. It presents the interest rate theory, interest rate derivatives and most important models of the interest rate. The LIBOR market model is calibrated to real market data. A pricing of a European swaption is performed according to Hull-White model and according to LIBOR market model, the results are compared. A Bermudan swaption is priced with the same models, which requires a different approach and the results are compared again.